Kekosongan Hukum Terkait Penangguhan dan Dimulainya Jangka Waktu Pembatasan Baru dalam Hukum Pajak - Nazhif Ali Murtadho; Sri Warjiyati (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2026)
The legal vacuum regarding the mechanism for suspending the statute of limitations on prosecution in Law No. 7 of 2021 creates a legal loophole that threatens state revenue. This study aims to comprehensively analyze the application of the principle of legal preference to fill this vacuum and to elucidate the disparity in statutes of limitations between the tax regime and the general criminal justice system. The research method employed is a legal-normative approach utilizing legislative, conceptual, and case-based analyses. The findings successfully demonstrate that the legal gap in tax legislation must be addressed by applying Article 138 of the National Criminal Code through the bridge provision of Article 187 of the National Criminal Code, thereby ensuring that investigative actions legally suspend and renew the statute of limitations. This study recommends that lawmakers undertake a fundamental revision of the Tax Regulation Harmonization Act to explicitly include a statute-of-limitations suspension clause.